Obtenção e caracterização de nanocompósitos à base de polihidroxialcanoato/atapulgita - Silva, Liliane Cardoso Alcantara (2010)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) PHBV is a biodegradable polyester produced by various microorganisms, which has been studied as an option for the production of disposable items in place of polymers derived from petroleum, thus contributing to the preservation of the environment. However, this thermoplastic has some disadvantages that limit its use in industrial scale applications: the relative difficulty of processing, low elongation at break, high degree of crystallinity and high cost of production relative to conventional polymers. An alternative to improve the properties of PHBV is the incorporation of small amounts of clay to the polymer, producing polymer /clay composites. The attapulgite is a typical fibrous clay. It has a surface area around 125 to 210 m2 /g and a cation exchange capacity from 20 to 30 milliequivalents per 100g of clay. The objective of this work was the production and characterization of biodegradable composites of poly (3-hydroxybutyrate-co- 3-hydroxyvalerate) - PHBV reinforced with natural attapulgite (AT) or attapulgite modified with hexadecylmethylammonium chloride (ATM) in different compositions ( 1, 3 and 5%). The composites were characterized by X-Ray Diffraction (XRD), Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and Nuclear Magnetic Resonance (NMR). The best results were obtained with incorporation of ATM levels greater than 3% (w /w). In these cases, it was observed reduction of the degree of crystallinity and decreasing of melting and glass transition temperatures as compared to PHBV films. However, the presence of attapulgite decreased the thermal stability of PHBV.